Lethal and behavioural toxicity of differently aged insecticide residues on European earwigs (Forficula auricularia) in the laboratory and in the field - Niedobová, Jana; Ouředníčková, Jana; Kudláček, Tomáš; Skalský, Michal (Environmental pollution (Barking, Essex, 2024)
Pesticide residues are an important topic in many environmental studies, but little is known about the effects of pesticide residues of different ages on beneficial arthropods. Therefore, in this study the activity of residues of three different ages of several commonly used insecticides on the behaviour and mortality of European earwigs was evaluated in the laboratory and the effect of the insecticides was verified in the field. All residues of the biorational SpinTor® (spinosad), Radiant SC (spinetoram), and the conventional Steward® (indoxacarb) showed significantly faster mortality progression compared to the control in the laboratory. All the Steward® residues caused a significant wave of erratic behaviour as the earwigs went through a deep and relatively long moribund stage and resurrected. We verified the effects of SpinTor® and Steward® on changes in earwig abundance and their behaviour in the orchard. Earwigs abundance was significantly lower 16 days after application of biorational SpinTor® and conventional Steward® which had a significantly more pronounced and longer lasting effect. The earwig population stabilised by day 53 after the insecticide applications. Field applications of insecticides had no effect on earwig behaviour and sex ratio. Our results show that older residues have a negative effect on European earwigs equal to that of fresh residues, although their degradation should occur. It is interesting to note that biorational insecticides may not be safer than chemical insecticides.
Keywords: predátorské chování; Insecta; insekticidy; Predatory Behavior; Behaviour; Earwigs; Animals; rezidua pesticidů; hmyz; Spinosyns; Residues; Pesticide Residues; zvířata; Toxicity; Auricularia; Insecticides; Indoxacarb